THE EFFECTIVENESS OF THE SYSTEMS OF DISTRIBUTED CONTROL THE SPEED OF THE CARS AT THE SORTING PATHS - Nazarov, O. A. (Science and Transport Progress, 2010)
The use of systems of the quasi–continuous adjusting the wagon speed on the marshalling tracks contributes to the improvement of indices of occupation quality of marshalling tracks with wagons. These indices characterize different sides of the occupation process and are incomparable among themselves. Therefore the technique for determination of the best parameters of the system by means of technical–economic comparison of variants is offered.